Africanisation of Curriculum - Le Grange, Lesley (South African Journal of Higher Education, 2018)
Even though the term curriculum has its origin in higher education it is neglected term in discourses on higher education. In the field of Curriculum Studies it is the school rather than the university curriculum that is mainly studied. This may be due to the relative autonomy that higher education institutions enjoy and the academic freedom granted its members. The downside of institutional autonomy and academic freedom in the South Africa context is that the Africanisation/decolonization of curricula has been left unaddressed by some universities. Twenty years into South Africa’s democracy it is an opportune time to again ask the key curriculum question: what knowledge is of most worth? What knowledge is of most worth to South African university students located on the African continent and who form part of a global society? In this paper I shall discuss the Africanisation of the university curriculum by drawing on insights from: the sociology of knowledge; indigenous knowledge; a different reading of the knowledge economy (different to the neoliberal reading). I shall argue that Africanisation of the university’s curriculum is dependent on understanding the active force of the term’s etymological root currere.